Durability of wood and wood-based products. Assessment of the effectiveness of masonry fungicide to prevent growth into wood of Dry Rot Serpula lacrymans (Schumacher ex Fries) S.F. Gray. Laboratory method. (26th May 2020) - British Standards Institution,
No abstract available